Analisis Kerentanan Tsunami Desa Talumolo Berbasis Sistem Informasi Geografis dan Parameter Multispektral untuk Mitigasi Bencana - Dicky Rahmansyah S Tone; Aang Panji Permana (Universitas Negeri Gorontalo, 2025)
The coastal area of Gorontalo City, particularly Talumolo Village, exhibits a high level of vulnerability to tsunamis due to its location within the active tectonic setting of the Sangihe–Halmahera Arc, which is directly adjacent to Tomini Bay. This study aims to analyze the level of tsunami vulnerability in Talumolo Village and its surrounding areas using a Geographic Information System (GIS) based on five multispectral parameters: elevation, slope, distance from rivers, distance from the coastline, and land cover. The data were obtained from the Geospatial Information Agency (BIG) in 2019 and processed using ArcGIS 10.8 through the Weighted Overlay Analysis method. Each parameter was classified into five vulnerability classes using a scoring system ranging from 1 to 9, and subsequently integrated using proportional weighting: elevation (30%), slope (25%), distance from the coastline (20%), distance from rivers (15%), and land cover (10%). The results reveal five classes of tsunami vulnerability: very high vulnerability covering 215.4 ha (23.7%), high vulnerability covering 198.2 ha (21.8%), moderate vulnerability covering 370.0 ha (40.7%), low vulnerability covering 67.4 ha (7.4%), and very low vulnerability covering 58.9 ha (6.4%). Areas with very high vulnerability are concentrated along the coastal zones of Pohe, South Leato, and Bugis, characterized by elevations below 20 meters and located within 500 meters of the shoreline. Elevation and slope are identified as the primary controlling factors, while densely populated land cover acts as an amplifying factor of potential impacts. The resulting vulnerability map represents the first spatial instrument for this area and can serve as a basis for disaster mitigation planning, hazard zoning, evacuation route development, and coastal spatial planning in Gorontalo City.